2021
DOI: 10.1007/s11547-021-01381-5
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in recurrent high-grade glioma: a single institution retrospective analysis on 92 patients

Abstract: Background High-grade gliomas are among the most aggressive central nervous system primary tumors, with a high risk of recurrence and a poor prognosis. Re-operation, re-irradiation, chemotherapy are options in this setting. No-best therapy has been established. Bevacizumab was approved on the basis of two Phase 2 trials that evaluated its efficacy in patients with recurrent glioblastoma. Materials and methods We have retrospectively review data of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Particularly in the recurrence setting, BEV presented response rates of approximately 30% in uncontrolled phase II trials [43]. About co-adjuvant chemotherapy with BEV, a randomized phase III trial tested the combination of BEV + lomustine versus lomustine alone, and results showed an improvement in PFS without OS changes in the combination group [44][45][46].…”
Section: Bevacizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in the recurrence setting, BEV presented response rates of approximately 30% in uncontrolled phase II trials [43]. About co-adjuvant chemotherapy with BEV, a randomized phase III trial tested the combination of BEV + lomustine versus lomustine alone, and results showed an improvement in PFS without OS changes in the combination group [44][45][46].…”
Section: Bevacizumabmentioning
confidence: 99%
“…The IL13 monomer IL-13Rα2 is a cancer germline antigen that has activity in the PI3K/AKT/mTOR pathway, expressed in approximately 75% of GB and associated with a worse prognosis [44,47]. Brown et al have studied the utility of IL-13Rα2-specific CAR T cells, observing a safe profile without significant positive results.…”
Section: Il-13rα2mentioning
confidence: 99%
“…Bevacizumab was approved for recurrent HGG on the basis of two phase 2 trials that evaluated its efficacy in patients with recurrent GB [56]. In 2014, two phase 3 trials revealed improved PFS, but not OS, after bevacizumab therapy combined to RT-TMZ [57,58].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In 2014, two phase 3 trials revealed improved PFS, but not OS, after bevacizumab therapy combined to RT-TMZ [57,58]. Recent analyses on limited groups of patients confirmed the efficacy of bevacizumab in improving the PFS of recurrent HGG patients with an acceptable toxicity profile [56,59]. Currently, the combination of re-irradiation with bevacizumab for recurrent HGG is common, but its efficacy is highly variable.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…At present, the clinical therapies for gliomas are surgical therapy, radiation therapy, chemotherapy, gene therapy, and other comprehensives (1,(71)(72)(73)(74). However, it is easy to relapse after these treatments, and the patients' survival rates are not significantly improved.…”
Section: The Application Of Phage Nanomaterials To Glioma Therapymentioning
confidence: 99%